Faktor-faktor yang mempengaruhi defisit transaksi berjalan Indonesia periode 1971-1999 - Edy Suandi Hamid; Nur Feriyanto; M. B. Hendrie Anto (Economic Journal of Emerging Markets, 2001)
Deficit of current account is a common phenomenon that happens in developing countries, as well as in Indonesia. Since 1960, Indonesia always faced Deficit of current account, except in some years (1974, 1979, and 1980). Although sometimes Deficit of current account is covered by surplus of capital flow, it still gives burden to neraca Pembayaran Indonesia.